(untitled) (Research, Society and Development, 2021)
Objective: to know the challenges and possibilities faced by social work in the educational field. Methodology: This is a narrative review of the literature whose guiding question was: "What are the challenges and possibilities of social work in the educational setting?" through bibliographic survey in the following databases: Scientific Electronic Library Online (SciELO), Academic Google, in addition to theses and dissertations from the CAPES Theses Bank. Development: Social service and education have a historical connection marked by conflicts, projects and societal struggles. In the educational scenario, social assistance works in favor of the democratization of education, permanence, conditions for entering and completing the school trajectory, ensuring access to education, student assistance and inclusive education. In their exercise, the social worker faces multiple manifestations of the social issue, which are expressed through the political, economic and cultural inequalities of social classes. Final Considerations: The insertion of the social worker in education becomes fundamental, both because of the existence of concrete demands and because of the possibilities for professional intervention, not just in student assistance.